Persepsi dan Partisipasi Masyarakat Adat atas Penetapan Kawasan Cagar Alam Teluk Bintuni di Distrik Wamesa Kabupaten Teluk Bintuni - Syaiful Anwar Killian; Selvi Tebaiy; Ishak Musaad (Program Pascasarjana Universitas Papua, 2021)
The indigenous peoples who live and live in the Bintuni Bay Nature Reserve Area in Wamesa District, consist of three villages, namely Mamuranu, Anak Kasih and Wasari. The economic activities carried out by indigenous peoples in the Bintuni Bay Nature Reserve conservation area are very high. This is related to the type of work or livelihood that the community is engaged in, namely fishermen (fish, shrimp and crab) at 43.75% and farming or gardening at 37.5%. Meanwhile, the public perception of the determination of the Bintuni Bay nature reserve area is quite varied. For example, the perception regarding the desire for community involvement in forest conservation in the Bintuni Bay nature reserve is very high (83.75%). Meanwhile, the perception of socialization or counseling from the Forestry Service / Agencies related to the management of the Bintuni Bay Nature Reserve is low (26.25%). Regarding the management of the Bintuni Bay nature reserve area, in general the community hopes to be actively involved in activities related to the Bintuni Bay Nature Reserve Area. In addition, the community wants to be allowed to carry out economic activities in the area, such as labor, gardening, fishing and others. Meanwhile, for the Government, the community hopes that there will be efforts to improve the community's economy and increase infrastructure and other public facilities, but while maintaining environmental sustainability forest in the Bintuni Bay nature reserve area.